Comparative Study of Antioxidant Levels (Vitamin E &Selenium) In Serum of Polycystic Ovary Syndrome Patients and Control - Hamad, Abdul Wahab Rzwki; Ahmad, Salman Ali; Rasheed, Farah Aqeel (Al-Nahrain Journal of Science, 2018)
Polycystic ovary syndrome (PCOS) is the most common endocrine disorder of reproductive women. The antioxidant (Vitamin E and Selenium) have important role in infertility and in PCOS. The aim of this study, to know the role of Vitamin E and Selenium during the phases of menstrual cycle and its effect on ovulation in (PCOS) patients and effect of body mass index in PCOS patients. This study, include 25 untreated and 26 treated PCOS patients comprised with 42 control. Vitamin E and selenium were measured by high performance liquid chromatography (HPLC) and atomic absorption spectrophotometer (AAS), respectively. Our results were observed vitamin E have significant (p<0.0005) between PCOS groups and control in pre-ovulation period (11-15) days and Selenium have highly significant difference (p<0.000005) between PCOS groups and control in each phase of menstrual cycle. From these results, concluded that vitamin E have role in ovulation and Selenium lowered significantly in untreated PCOS, suspecting presence of oxidative stress.